Children's Facial Trustworthiness Judgments: Agreement and Relationship with Facial Attractiveness - Ma, Fengling; Xu, Fen; Luo, Xianming (Frontiers in Psychology, 2016)
This study examined developmental changes in children's abilities to make trustworthiness judgments based on faces and the relationship between a child's perception of trustworthiness and facial attractiveness. One hundred and one 8-, 10-, and 12-year-olds, along with 37 undergraduates, were asked to judge the trustworthiness of 200 faces. Next, they issued facial attractiveness judgments. The results indicated that children made consistent trustworthiness and attractiveness judgments based on facial appearance, but with-adult and within-age agreement levels of facial judgments increased with age. Additionally, the agreement levels of judgments made by girls were higher than those by boys. Furthermore, the relationship between trustworthiness and attractiveness judgments increased with age, and the relationship between two judgments made by girls was closer than those by boys. These findings suggest that face-based trait judgment ability develops throughout childhood and that, like adults, children may use facial attractiveness as a heuristic cue that signals a stranger's trustworthiness.